Ability Analysis of Providing Explanations and Strategies in Learning Science - Lia Kartina; Nurmeimana Nurmeimana; Ikechuku Abamba; Amar J. Aswad (Journal Evaluation in Education (JEE), 2023)
Purpose of the study: This descriptive study aims to analyze science learning based on students' High Order Thinking Skills, which can be seen from the thinking skills of students in junior high schools. Methodology: This research was conducted at Junior High School State 21 Jambi City using a mixed research method with an explanatory analysis design with two instruments instrument for the quantitative approach and interview sheets for the qualitative approach. The research subjects were 58 students of class VIII. The concept tested is material about lens refraction, divided into ten questions. Main Findings: Five indicators tested are the ability to provide essential explanations (MPD) and strategies and tactics. After analyzing the student's answers, the average MPD skills were 2.40, and strategy and tactics were 2.48. This critical thinking skill is good because the teacher also provides space for students to be active in learning so that students often ask questions and analyze the material presented in learning science. Novelty/Originality of this study: The novelty of this study is that analyzing HOTS-based science learning can improve students' critical thinking skills so that students can be active in asking questions and analyzing the material. With necessary thinking skills, students can be more open to differences of opinion, and students can still be objective with the sources of knowledge that they have before.